"Not Rural but Not Urban": Community Governance in China's Urban Villages*. (23rd July 2015) - Tang, Beibei
Abstract: China's urbanization has created a large number of urban villages which, although they have been transferred to urban administration, have maintained their collective economies. Using a comparative perspective, this article investigates how villagers, the village collectives and the urban administration organize community governance in three urban villages on the fringes of the cities of Guangzhou, Wuhan and Shenyang. The findings suggest that successful village collective shareholding companies play a leading role in community governance by providing villagers with economic and social welfare, subsidizing community administration services, and mobilizing residents. The comparative analysis also shows that village shareholding companies employ different mechanisms based on the varied histories of their village collective economies, the ability of the village collectives to mobilize resources, and the degree to which the village collectives are engaged in the grassroots administrative structure. The article argues that the "not rural but not urban" governance mode of the urban villages illustrates China's fragmented urbanization planning. At the same time, it illuminates the dynamics of state–society relations during China's urbanization and how landless villagers and village collectives respond to urban transformation by adopting different strategies to preserve their individual and collective interests. 摘要: 中国的城市化产生了大量的"村转居"社区。这些社区一方面属于城市行政管理, 另一方面又保留着原有的村集体经济。本文对广州, 武汉和沈阳三地"村转居"社区的管理模式进行了比较研究。其结果显示, 成功的村集体股份公司通过向村民提供生活和社会保障, 承担部分社区服务, 和组织居民参与社区活动, 从而在"村转居"社区治理中处于主导地位。由于当地集体经济的发展历程, 其组织动员居民的能力以及参与社区管理的程度存在差异, 三地的村集体股份公司表现出不同的"村转居"社区管理模式。本文揭示了"村转居"社区存在"村不村, 居不居"的管理模式。这一方面是因为城市化进程缺乏全面系统的规划。另一方面也体现了在城市化过程中, 失地农民与村集体经济采用多样化的方式来维护个人和村集体的利益, 从而影响了社会与国家组织之间的互动。